Nightshift work job exposure matrices and urinary 6-sulfatoxymelatonin levels among healthy Chinese women - Ji, Bu-Tian; Gao, Yu-Tang; Shu, Xiao-Ou; Yang, Gong; Yu, Kai; Xue, Shou-Zheng; Li, Hong-Lan; Liao, Linda M; Blair, Aaron; Rothman, Nathaniel; Zheng, Wei; Chow, Wong-Ho (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVE ': 'Six-sulfatoxymelatonin (aMT6s) is a primary urinary metabolite of melatonin. We examined the association between aMT6s levels and shift work estimated by a job exposure matrix (JEM) among healthy participants of the Shanghai Women’s Health Study. ' ' METHODS ': 'Creatinine-adjusted aMT6s levels were measured in the urine samples of 300 women and related to JEM shift work categories. ' ' RESULTS ': 'Adjusted geometric means of aMT6s levels from urine samples collected before 08:00 hours were lower among persons holding nighttime shift work jobs. The adjusted aMT6s levels (ng/mg creatinine) were 8.36 [95% confidence intervals (95% CI) 4.47–15.6], 6.37 (95% CI 3.53–11.5), 6.20 (95% CI 3.33–11.5), 3.81 (95% CI 2.02–7.19), and 3.70 (95% CI 1.92–7.11) from the lowest (never held a shift work job) to the highest (current job likely involved all-night shift work) shift work JEM scores (P=0.05). ' ' CONCLUSION ': 'Our results indicate that nightshift work JEM scores were significantly and inversely associated with aMT6s levels in early morning spot urine samples collected between 07:00–08:00 hours.
Keywords: aMT6s; cancer; China; job exposure matrix; melatonin; night shift; nighttime work; shift work; urinary 6-sulfatoxymelatonin; urine sample; woman